Gender Inequality Analysis Represented in “Little Women” by Louisa May Alcott - Mareta, Dinar Rosiana; Afriana, Afriana (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Gender inequality is the unequal allocation of opportunities and rights, among people of various genders. This commonly works against one gender, typically women. This research aims to analyze Louisa May Alcott's